Relationship between Subclinical Hypothyroidism and Uremic Pruritis in Hemodialysis Patients - Kotb, Essam; El Mancy, Ismail Mohamed; Mohamed, Ibrahim Ghounim Ramadan; Ayoub, Hazem Sayed Ahmed; Rashed, Al-Sayed M; El-Nasser, Waleed S; Hamed, Hani Ismail; Aladl, Hossam Aladl; Sabrh, Mostafa; Eliwa, Ahmed; Ghamry, Esam M; Abdelhamed, Mohamed R; et al. (Endocrine, metabolic & immune disorders drug targets, 2024)
Uremic pruritus (UP) is one of the most distressing symptoms in hemodialysis (HD) patients. Subclinical hypothyroidism (SCH) is a biochemical condition with high prevalence in HD patients. The present multicentric study aimed to assess the relationship between UP and SCH in HD patients. The present cross-sectional study included 328 HD patients. All patients were submitted to careful history through clinical examination and standard laboratory assessment. Pruritis was evaluated using the pruritis visual analog scale (VAS). Patients were diagnosed with SCH if they had TSH levels above the upper limit of the normal reference range in association with normal free thyroxine (FT4) levels. Among the studied patients, there were 196 patients (59.8 %) with UP. Comparison between patients with UP and patients without revealed that patients in the former group had significantly longer HD duration (median (IQR): 47.5 (27.0-72.5) versus 36.0 (23.0-50.5) months, p < 0.001) and lower Kt/v (median (IQR): 1.4 (1.09-1.7) versus 1.54 (1.12-1.91), p = 0.009). Moreover, they had significantly higher ferritin (median (IQR): 653.0 (526.0-800.0) versus 628.0 (470.8- 716.0) ng/mL), hsCRP (median (IQR): 12.0 (8.0-14.0) versus 8.0 (6.0-9.0) mg/dL, p < 0.001) and TSH levels (median (IQR): 4.34 (1.98-5.2) versus 3.34 (1.9-4.85) μIU/ml) with a significantly higher frequency of SCH (45.9 % versus 28.8 %, p = 0.002). Logistic regression analysis identified hemodialysis duration (OR (95%) CI): 1.02 (1.009-1.028), p < 0.001), ferritin levels (OR (95% CI): 1.002 (1.001-1.003), p < 0.001), and SCH (OR (95% CI): 0.54 (0.32-0.89), p = 0.016) as significant predictors of UP. The present study suggested a possible link between SCH and the development of UP in HD patients.